TREATMENT OF CHRONIC HEPATITIS-C WITH STANDARD INTERFERON AND RIBAVIRIN - Jadoon, Shakeel Ahmad; Jadoon, Habib Ahmad; Nazar, Hassan Shahzad (Journal of Ayub Medical College Abbottabad, 2014)
Background: The prevalence of hepatitis-C is on the rise in Pakistan. Treatment of chronic hepatitis-C with pegylated interferon is expensive as compared to standard interferon. The objective of the study was to find out the end treatment response rate with standard interferon and ribavirin. Methodology: This case series study was conducted in Ayub Teaching Hospital Abbottabad and Orush General Hospital over a period of two years.170 patients were included in the study. These patients were HCV PCR positive either by qualitative or quantitative assay, had no other comorbidity or decompensated disease. The treatment started with standard interferon and ribavirin for six months. After the six months at the end of treatment again HCV PCR assay was done to detect hepatitis-C virus in the blood. Those who were PCR negative were responders and positive are non-responder. Results: The cumulative response rate was 73.5%, both sexes responded equally. Patients below 30years had the highest response rate and similarly patients having normal liver had better response than those having any degree of fibrosis. Baseline haemoglobin and ALT level did not have significant effect on treatment. Conclusion: Standard interferon is equally effective and comparable with the pegylated interferon which is costly and out of reach of many patients. It is therefore recommended, that combination of standard interferon and ribavirin may be the first line of treatment for chronic hepatitis-C treatment in Pakistan and pegylated interferon may be reserved for non-responders or relapsed cases Keywords: Hepatitis-C, Interferon, Ribavirin, Cirrhosis, ALT